Modelling of reinforced concrete beam by using plasticity approach - Mansor, Nur Fatiha Nadia (2016)
Reinforced concrete structure is a composite material made of fresh concrete and steel bars most commonly used in construction industry due to economic, efficiency, and strong in sustained stress. Even though reinforced concrete is widely used with many modification applied to increase the strength and durability, structure are still exposed to failure due to limitation of plastic behaviour knowledge on concrete. The objectives of this study are to determine formula of moment-curvature and load-displacement; ultimate loads to achieve yield state, the moment-curvature and load-displacement relationships of reinforced concrete and verify the applicability of the proposed model by comparing the predicted behaviours with those observed in experimental results. This study is carried out created a model of simply-supported beam with two concentrated load in symmetrically way. MATLAB was chosen in this study to determine the plastic behaviour of concrete beam under bending load. The results on moment-curvature and load-displacement formula, ultimate loads, moment-curvature and load-displacement relationships and comparison of results are presented in this report. Based on the analysis, it is found that the moment and displacement of reinforced concrete beam is affected by load applied and plasticity behaviour of a reinforced concrete beam. Moreover, the formulation of moment-curvature and load-displacement of reinforced concrete beam is successfully developed.